Perioperative Chemotherapy on Survival in Patients With Upper Urinary Tract Urothelial Carcinoma Undergoing Nephroureterectomy: A Population-Based Study - Zhai, Ting-Shuai (Front Oncol, 2020)
Objectives: To estimate the stage-specific impact of perioperative chemotherapy on survival for upper urinary tract urothelial carcinoma (UTUC) patients treated with nephroureterectomy (NU). Methods: Overall, 7,278 UTUC patients treated with NU from 2004 to 2015 were identified within the SEER database. Kaplan–Meier plots were used to elucidate overall survival (OS) and cancer-specific survival (CSS) rates. Multivariable Cox regression analyses were used to test the impact of chemotherapy on survival rates, after stratifying according to pathological stage. Results: Chemotherapy was performed in 17.3% of patients and in 5.7, 11.5, 25.4, and 51.3% of patients with, respectively, pT1, pT2, pT3, and pT4 disease (P < 0.001). In multivariable analyses, perioperative chemotherapy was associated with a lower OS in pT2 patients and a lower CSS in pT1 disease (both P < 0.05), while predisposed to a higher OS in pT3 and pT4 patients (both P < 0.01). Moreover, perioperative chemotherapy was prone to a higher OS or CSS in pN+ disease compared to no chemotherapy (both P < 0.01). Conclusion: Perioperative chemotherapy was more frequently performed in locally advanced UTUC patients. The beneficial effect of chemotherapy on OS was evident in pT3/pT4 and pN+ patients. In addition, a clear CSS benefit was observed in patients who received chemotherapy for pN+ UTUC, while perioperative chemotherapy may reduce CSS for pT1 and OS for pT2 patients following NU.